2017
DOI: 10.1371/journal.pone.0179477
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of gene expression in contrasting maize inbred lines under field drought conditions reveals the significance of transcription factors in drought tolerance

Abstract: Drought is a major threat to maize growth and production. Understanding the molecular regulation network of drought tolerance in maize is of great importance. In this study, two maize inbred lines with contrasting drought tolerance were tested in the field under natural soil drought and well-watered conditions. In addition, the transcriptomes of their leaves was analyzed by RNA-Seq. In total, 555 and 2,558 genes were detected to specifically respond to drought in the tolerant and the sensitive line, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 83 publications
1
55
0
Order By: Relevance
“…ARFs play key roles in plant growth and development through the regulation of expression of auxin response genes which can include transcription factors (Li et al 2016). They are also thought to contribute to drought tolerance (Feng et al 2015; Zhang et al 2017). In maize shoots, Feng et al (2015) indeed showed that the expression of ZmGH3.8 was induced by auxin and reduced under polyethylene glycol treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARFs play key roles in plant growth and development through the regulation of expression of auxin response genes which can include transcription factors (Li et al 2016). They are also thought to contribute to drought tolerance (Feng et al 2015; Zhang et al 2017). In maize shoots, Feng et al (2015) indeed showed that the expression of ZmGH3.8 was induced by auxin and reduced under polyethylene glycol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In maize shoots, Feng et al (2015) indeed showed that the expression of ZmGH3.8 was induced by auxin and reduced under polyethylene glycol treatment. More recently, Zhang et al (2017) identified 13 ARFs as differentially expressed between a drought tolerant and a drought sensitive maize line under different drought scenarios. The second region is located on chromosome 5 where we identified two transcription factors, a SBP gene (GRMZM2G111136) and a C2C2-CO-like gene (GRMZM2G148772), as candidate genes underlying QTLs for key plant growth and transpiration traits, pQTLs for seven proteins and coQTLs for three modules.…”
Section: Discussionmentioning
confidence: 99%
“…ZmWRKY40 432 (GRMZM2G120320, rank 9) was shown to confer drought resistance when it was 433 overexpressed in A. thaliana (Wang et al, 2018b). ZmXLG3b (GRMZM2G429113, 434 rank 1), encoding a guanine nucleotide-binding protein predicted to be involved in the 435 response to desiccation, was found to be downregulated in the drought-tolerant 436 H082183 line but upregulated in the drought-susceptible maize line Lv28 under 437 severe drought stress versus control conditions (Zhang et al, 2017). Moreover, 438…”
Section: Exploration Of New Maize Genes Predicted To Be Involved In Bmentioning
confidence: 99%
“…These findings suggest that altered lncRNAs may be involved in "plant hormone signal transduction" and regulated differently in the two genotypes. The up-regulation of ABF in response to drought stress can trigger stomatal closure and seed dormancy [94]. The down-regulation of ABF in response to re-watering led to weakened ABA signal, which may alleviate rapeseed seedling growth inhibition by ABA.…”
Section: Gibberellin (Ga) Plays An Important Role In All Stages Of Plmentioning
confidence: 99%